The role of self-esteem and self-control on smoking behavior man: case study among college students - Mujidin, Mujidin; Rustam, Husnul Khotimah; Rizqyanto, Muhammad (Intelektual Pustaka Media Utama, 2024)
Smoke and a collection of components in cigarettes can cause very serious diseases. More precisely can disrupt health and its impact on individual health psychology. The purpose of this study is to explore how much the role of self-esteem and self-control of the smoking behavior of students in Yogyakarta. This study uses cross sectional studies with random sampling techniques. Respondents obtained were 75 students who were actively smoking cigarettes. The measuring instruments given include self-esteem scale, self-control scale and smoking behavior scale. The findings of this research explain that when students prioritize positive self -esteem then they tend to reduce or not smoke. In addition, self-control can limit the desire of students to reduce or stop smoking. Students who smoke at least do not do that in front of many people or avoid the crowd so as not to make other people tight or cough. There are still a number of other things that affect smoking behavior with cognitive, social, and cultural treatment. The nation's expectations and hopes that students would continue to be healthy, optimistic, and productive. Smoking research is very important to trace its clause so that it can help improve the health level of human life in the future.